Impact of high atmospheric carbon dioxide on the biotic stress response of the model cereal species Brachypodium distachyon - Trémulot, Lug; Macadré, Catherine; Gal, Joséphine; Garmier, Marie; Launay-Avon, Alexandra; Paysant-Le Roux, Christine; Ratet, Pascal; Noctor, Graham; Dufresne, Marie (Frontiers in Plant Science, 2023)
Losses due to disease and climate change are among the most important issues currently facing crop production. It is therefore important to establish the impact of climate change, and particularly of high carbon dioxide (hCO2), on plant immunity in cereals, which provide 60 % of human calories. The aim of this study was to determine if hCO2 impacts Brachypodium distachyon immunity, a model plant for temperate cereals. Plants were grown in air (430 ppm CO2) and at two high CO2 conditions, one that is relevant to projections within the coming century (1000 ppm) and a concentration sufficient to saturate photosynthesis (3000 ppm). Improved shoot development was observed at both 1000 and 3000 ppm. A transcriptomic analysis in the three conditions pointed to an increase in primary metabolism capacity under hCO2. Alongside this effect, up-regulation of genes associated with secondary metabolism was also observed. This effect was especially evident for the terpenoid and phenylpropanoid pathways, and was accompanied by enhanced expression of immunity-related genes and accumulation of salicylic acid. Pathogen tests using the fungus Magnaporthe oryzae revealed that hCO2 had a complex effect, with enhanced susceptibility to infection but no increase in fungal development. Overall, the study reveals that immunity to B. distachyon is modulated by growth at hCO2 and allows identification of pathways that might play a role in this effect.